INDUKSI TUNAS MIKRO PISANG KULTIVAR AMBON NANGKA (Musa sp.) SECARA IN VITRO - Rendie Prasetyo; Sugiyono Sugiyono; Lucky Prayoga (Universitas Tidar, 2020)
The research was carried out to determne the best concentration of kinetin and activated charcoal to stimulate the shoot growth of Ambon Nangka banana cultivar. This research used a Completely Randomised Design (CRD) arranged factorials. The first factor was the concentration of kinetin with 4 levels i.e. 15 µM, 20 µM, 25 µM and 30 µM. The second factor was the concentration of activated charcoal with 4 levels i.e. 0 gL-1; 1 gL-1; 2 gL-1; and 3 gL-1. Each treatment combination was repeated 3 times, which resulted in 48 experimental units. The parameters measured were the shoot emergence time, number of shoots, shoot length, number of roots and root length. The data were analyzed using an analysis of variance at 95% and 99% level of confidences. The research results showed that the interaction between kinetin and activated charcoal had no effect on shoot length of Ambon Nangka banana cultivar. It was also found that the addition of 20 µM kinetin without any added activated charcoal resulted in the highest shoot number of Ambon Nangka banana cultivar.Keywords: Ambon Nangka, kinetin, activated charcoal